(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
The experimental work was carried out at the DemonstrationFarm of the Faculty of Agricultural Sciences and Environment,University of Gedarif in the northern area of Gedarif State for fourseasons (2006/07,2007/08 , 2008/09 and 2009/10) to investigate the effectof some water harvesting techniques on the productivity of two sorghumcultivars in north Gedarif. The experiment was laid out in a split plotdesign with three replications; the main plots assigned to four waterharvesting techniques. Closed furrow at one end, open furrow at the twoends, closed furrow at the two ends, and a terrace in addition to traditionalfarmers practice as a control treatment. Sub plots were assigned to twosorghum cultivars: Arfa Gadamac and Wad Ahmed That water harvestingtechniques significantly increased the storage capacity of the soil whichwas reflected significantly in increasing the grain yield by 56%, 50% 33%and 17% for the open furrow at the one end, closed furrow at the twoends, open furrow at the two ends and terrace, as compared to the flat(control), respectively. Arfa Gadamac variety gave a high grain yield(414.5 kg/fed) compared to Wad Ahmed (284.7kg/fed). From this study itcan be concluded that closed furrow at one end, closed furrow at twoends, open furrow at two ends techniques could be used successfully bysmall farmers in north Gedarif area to increase sorghum productivity.Based on its low yield, Wad Ahmed sorghum cultivar is notrecommended for north Gedarif area even under water harvestingtechniques